Intraocular lens-edge design and material factors contributing to posterior-capsulotomy rates: comparing Hoya FY60AD, PY60AD, and AcrySof SN60WF - Morgan-Warren PJ (Dove Medical Press, 2013)
Peter J Morgan-Warren, JM Alaric SmithVictoria Eye Unit, Hereford County Hospital, Hereford, UKPurpose: To compare neodymium-doped yttrium aluminum garnet laser posterior capsulotomy (LPC) rates between the Hoya FY60AD, Hoya PY60AD, and Alcon AcrySof SN60WF intraocular lenses (IOLs) after routine cataract surgery.Methods: In this retrospective comparative study, patients undergoing uncomplicated cataract surgery over a 3-year period were included, and those subsequently undergoing LPC were identified from laser clinic records. LPC rates at 2 years postoperatively were compared between the round-edged Hoya FY60AD , the newer sharp-edged Hoya PY60AD three-piece IOLs, and the one-piece AcrySof SN60WF IOL.Results: A total of 1,265 cataract operations were included, and 49 eyes (3.9%) underwent LPC within 2 years of surgery. Twenty-eight of 315 eyes (8.9%) implanted with the FY60AD underwent LPC by 2 years, compared to eleven of 254 (4.3%) with the newer sharp square-edged PY60AD and ten of 696 (1.4%) with the one-piece SN60WF (P < 0.05, Chi-squared analyses).Conclusions: The newer, sharper-edged Hoya PY60AD IOL has a lower LPC rate than the Hoya FY60AD IOL at 2 years post-cataract surgery. The one-piece AcrySof SN60WF has a lower LPC rate than both the three-piece Hoya IOLs in the same time period postoperatively. Variations in IOL-edge design and material effect may have contributed to the different rates observed.Keywords: intraocular lenses, Nd:YAG laser capsulotomy, posterior-capsule opacification